Secure Marketing Website - Sabeb, A. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The Internet provides business with new methods of reaching and interacting with Â·customers as well as improving inter and intra business communication. In this research, a soft.ware marketing web site with a security tools is designed and implemented to protect the customer pers.onal information and payment information when a customer tries to pay a software package. A new protectior.t method is suggested to protect the c.ustomer payment information passing through the network. This method is ca:Jied a covert channel , because it use two ports to send and receive the payment information and downlqads of oftware packages to the customer and these ports are dynamical and changes every time. The modern techniques are used in building the web site and its security like ASP. NET, XML with their security rules, SQL database management, JavaScript and Visual Basic Script for- encryption and controlling the communication operation, and Cookies for the chosen ports of covert channel. The encryption technique (MD5 technique) is also used to protect the important information and payment pages transfer between both directions.